Karakterisktik Pasangan Usia Subur Dengan Penggunaan Metode Kontrasepsi Jangka Panjang - Fatmawati, Tresna; Fransisca, Lidya; Adriani, Adriani; Izalika, Izalika (STIKES Al-Su’aibah, 2024)
One of the various National Population and Family Agency efforts to reduce maternal mortality is to increase the use of Long-Term Contraceptive Methods (MKJP). According to data in Banyuasin Regency 2023, MKJP IUD users were 969 (1%), implants 15,629 (15.7%), MOW 1,699 (1.7%) and MOP 134 (0.1%) and non-MKJP injections 65,972 (66, 2%), pills 13,061 (13.1%), condoms 2,224 (2.2%). The low rate of use of MKJP is considered to cause several problems, such as a high rate of failure to delay or reduce the risk of having children. This research used a descriptive research design with a cross sectional approach with the sampling technique used was a total sampling technique totaling 35 respondents. From the research results, it was found that 60% of PUS were >35 years old, 40% were of parity >2, 60% had higher education and 34.3% were using MKJP. It is hoped that the results of this research can become study material for health workers to encourage the public, especially PUS, to use MKJP.